Influence of provitamin A carotenoids on iron, zinc, and vitamin A status - Hess, Sonja Y.; Thurnham, David I.; Hurrell, Richard F. (International Food Policy Research Institute, 2005)
Bioavailable iron, vitamin A, and zinc are mainly provided in the human diet by animal source foods. In the developing world, where poorer individuals consume predominantly plant-based diets, deficiencies of these micronutrients are common and can occur in the same individual. Infants, children, and pregnant and lactating women are most at-risk of deficiency because of their extra requirements for growth...In the context of plant breeding and biotechnology to enhance the levels of — or improve the bioavailability of — iron, provitamin A carotenoids, and zinc to combat micronutrient malnutrition, this review discusses in detail the influence of vitamin A status on iron utilization and the consequent impact on iron status.